(untitled) (Research, Society and Development, 2021)
Mood disorders are among the most prevalent health problems affecting the young adult population, especially academics of higher education. This scenario may be even more evident with the social isolation related to COVID-19. The aim of this study was to investigate symptoms of stress, depression and anxiety in academics from private institutions of higher education, under social isolation. The study was performed using questionnaires to obtain socioeconomic data and the Anxiety, Depression and Stress Scale (DASS-21), using an online platform. The results demonstrated that most participants had symptoms of stress, anxiety or depression. People with mood disorders had severe scores on the DASS-21. In addition, there was a higher prevalence of severe and extremely severe symptoms in females when compared to males. Finally, there was a negative correlation with age, demonstrating that, as younger, higher the score. The participants had significant scores of mood disorders probably because the majority work and study. In addition, they probably increase the susceptibility to these conditions with COVID-19 pandemic. The predominant age corresponds to the so-called emerging adult phase and the majority of women is probably related to the fact that most health sciences courses participated in the research and had predominantly women.